Implementasi Pertanian Berkelanjutan melalui Pembuatan Pupuk Organik Cair di Karot, Kabupaten Manggarai - Choirunnisa, Jessyca Putri; Haim, Kristina; Duru, Laurensius Retno; Namur, Valentina; Faldido, Rilobertus; Mensi, Camelia Ronildis; Bana, Maryance Vivi Murnia; Cordanis, Astried Priscilla (Institut Pertanian Bogor, 2024)
Excessive use of synthetic fertilizers causes a decrease in soil fertility, which can reduce crop production. Making liquid organic fertilizer (POC) from vegetable and fruit waste can reduce the use of synthetic fertilizers and support sustainable agriculture. The Golo Curu Permai farmer group has never implemented sustainable agriculture. This activity aims to reduce synthetic fertilizers' use to support sustainable agriculture and increase the knowledge and skills of farmer groups in producing liquid organic fertilizers independently. This activity was carried out at the Golo Curu Permai farmer group in Karot Village, Langke Rembong District, Manggarai Regency, with a total of 15 participants and through activity methods in the form of coordination and field surveys, extension, training or demonstration and evaluation. Evaluation is carried out by analyzing the initial test results before training (pre-test) and after training (post-test). The results of this activity show that the knowledge and skills of farmer groups after participating in training in making POC from organic waste increased by 30% from 50% to 85%.